Measurement of in vivo proliferation in human colorectal mucosa using bromodeoxyuridine. Issue 1 (January 1992) - Potten, C S; Kellett, M; Roberts, S A; Rew, D A; Wilson, G D
Abstract : In vivo bromodeoxyuridine (BrdUrd) labelling of the human large bowel was performed and a detailed histochemical localisation of label in sections of crypts was undertaken using a monoclonal antibody to BrdUrd containing DNA. Flow cytometric studies on extracted nuclei were also performed (data presented elsewhere). The average crypt in the human large bowel (excluding the rectum) was 82 cells in height and 41 cells in circumference, with a total of about 2000 cells (assuming a topographical correction factor of 0.6). Ten per cent of the cells were replicating their DNA--that is, were in the S phase of the cell cycle--and 0.4% were in mitosis. The median position for the labelling index versus cell position frequency plot is at the 20th cell position--at a quarter of the crypt height. The lower and upper limits of the cell proliferation are given by the 5th and 95th percentiles at cell positions 4 and 43 respectively. The peak labelling index is about 30% and it occurs at cell position 15. The labelling index at the crypt base, the probable stem cell zone, is about 14%, suggesting that these cells have a longer cell cycle. Taking a value of 8.6 hours for the duration of the S phase (deduced from the flow cytometric data) and assuming a growth fraction of 1.0 for the mid-crypt, these data provide an estimate of about 30 hours for the cell cycle time. The rectal crypts are about the same size but contain about 30% fewer S phase cells. The data also yielded a per cent BrdUrd labelled mitosis curve.